2019
DOI: 10.3390/molecules24173202
|View full text |Cite
|
Sign up to set email alerts
|

Cordidepsine is A Potential New Anti-HIV Depsidone from Cordia millenii, Baker

Abstract: Chemical investigation of Cordia millenii, Baker resulted in the isolation of a new depsidone, cordidepsine (1), along with twelve known compounds including cyclooctasulfur (2), lup-20(29)-en-3-triacontanoate (3), 1-(26-hydroxyhexacosanoyl)glycerol (4), glyceryl-1-hexacosanoate (5) betulinic acid (6), lupenone (7), β-amyrone (8), lupeol (9), β-amyrin (10), allantoin (11), 2′-(4-hydroxyphenyl)ethylpropanoate (12) and stigmasterol glycoside (13). Hemi-synthetic reactions were carried out on two isolated compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Depsides and depsidones are lichen-derived secondary metabolites with several biological activities such as anticancer, antibacterial, antioxidant, antiparasitic, and antiviral [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. We extracted, purified, and screened the anti-DENV2 activity of Usnea baileyi , Usnea aciculifera , and Parmotrema dilatatum and found three compounds with inhibitory activity against DENV2 over 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depsides and depsidones are lichen-derived secondary metabolites with several biological activities such as anticancer, antibacterial, antioxidant, antiparasitic, and antiviral [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. We extracted, purified, and screened the anti-DENV2 activity of Usnea baileyi , Usnea aciculifera , and Parmotrema dilatatum and found three compounds with inhibitory activity against DENV2 over 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Their core structures are composed of orcinol [ 7 ]. Depsides and depsidones with various biological activities have been reported, including antioxidant [ 8 , 9 ], antimicrobial [ 10 , 11 ], antiparasitic [ 12 ], anticancer [ 13 , 14 ], and antiviral [ 15 , 16 , 17 ]. A previous study showed that atranorin and its derivatives exhibited anti-hepatitis C virus (HCV) activity in the entry and replication stage [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cordia millenii investigation resulted in a new analog, 6 that was assigned by spectral and X-ray analyses. This compound had promising HIV-1 integrase efficacy (IC 50 4.65 µM) in comparison to chicoric acid (IC 50 0.33 µM) ( Dongmo Zeukang et al, 2019 ).…”
Section: Bioactivities Of Depsidonesmentioning
confidence: 99%
“…Major uses of Cordia millenii tree are in the area of timber industry and traditional herbal medicine [ 30 , 32 , 33 ]. In African phytomedicine (where it is an indigenous plant), various parts are used to treat or manage fevers, cough, stomachache, toothache, inflammatory-related disorders, HIV, diarrhea, dysentery, ringworm, and worm infestation [ 30 , 33 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals isolated from different parts of Cordia millenii plant include glycosides (triterpenoids), resins, lipids, sugars, alkaloids, essential oils, tannins, flavonoids (phenolic compounds), steroids, saponins, terpenoid benzoquinones called cordiachromes A–F, and the latest being cordidepsine [ 29 , 34 , 36 , 37 ]. When the stem is slashed, viscous liquid oozes out freely after 7–10 days and continues for several weeks.…”
Section: Introductionmentioning
confidence: 99%